NILAI EKONOMI NIRA SAWIT SEBAGAI POTENSI PEMBIAYAAN PEREMAJAAN KEBUN KELAPA SAWIT RAKYAT - Muhammad Akmal Agustira; Donald Siahaan; Hasrul Abdi Hasibuan (Jurnal Penelitian Kelapa Sawit, 2019)
Oil palm smallholder currently are more than 25 years old and have to be replanted. However, many smallholders have facing difficulties in replanting especially related to investment and loss of income during the period of immatature. Palm trunks from replanted plants have potential economic value by utilizing sap obtained by tapping inflorescences of oil palm to make brown sugar. This study aims to assess the economic value of oil palm brown sugar as a potential financing of oil palm plantation peremajaan. The study was conducted in the village of Lau Tador, Sei Suka District, Batu Baral Regency North Sumatra. The research method used was on farm participatory research survey and focus group discussions were carried out farm business analysis. Research shows that oil palm trunks have considerable economic value potential. The economic value of 1 palm trunk for oil palm brown sugar (not yet processed/straightened before being cut) is IDR. 15,813 (IDR 1,897,500 per ha). Whereas if processed into oil palm brown sugar has a potential net income per ha of IDR 18,421,500 to IDR 22,866,325 with financial analysis carried out. This potential can help smallholders living costs and up keep costs as long as immatature. To optimize the economic potential of production, it is carried out on a wide scale through the development of farmer groups or cooperatives. Through cooperatives will be managed in an organized manner including funding, technical, production, and marketing. The utilization oil palm brown sugar can be used as one of the activities in the oil palm smallholder replanting program (PSR) which is the government's main program.